Afterlife belief: between spiritual bypass, coping and emergence during the grieving process (Paliativní medicína, 2023)
The article conceptually defines the differences between spiritual bypass, coping, and emergence concerning afterlife belief. The concepts are explored regarding to spirituality manifestations, impacts, and characteristics. I used typology defined by Jaakkola as methodological tool for the paper. Possible recommendations for professional support for the bereaved are drawn from the typology.
Keywords: Spiritual bypass; Spiritual coping; Spiritual emergence; Continuing Bonds; Afterlife; Typology; Grief; Mourning; Bereavement